Tradisi Melemang: Studi Psikologi Indigenous terhadap Persepsi Masyarakat Melayu di Era Modernisasi - Dira Utami; Awang Ringko (LPPM Institut Pendidikan Nusantara Global, 2025)
This article examines the Melemang tradition, a cultural practice of the Malay community traditionally performed during Islamic religious celebrations, which is currently facing significant challenges in its preservation amid modernization. The main focus of this study is to emphasize the importance of understanding cultural traditions from a local perspective in order to maintain their connection to collective identity. The Melemang tradition represents a form of cultural heritage that is deeply rooted in the social life of the Malay community and reflects shared values, social cohesion, and cultural continuity. The purpose of this study is to explore the meaning of the Melemang tradition within the framework of Indigenous Psychology. This research employs a contextual reflective approach, linking cultural practices with contemporary social dynamics in the community. The findings are expected to contribute to a deeper understanding of local cultural values and to strengthen awareness of the importance of preserving cultural traditions through a psychological perspective based on local wisdom.